Newspaper Reporting of Suicides in Thailand : Compliance with WHO Media Guidelines - Lotrakul, Manote; Suwannakan, Patthira (Journal of the Psychiatric Association of Thailand, 2022)
Objective: To study the newspaper reporting of suicide in Thailand in terms of their compliance with the World Health Organization’s suicide news reporting guidelines for 2017. Methods: We conducted a 6-month (January 1, 2019 – June 30, 2019) retrospective descriptive study on three newspapers reporting of suicides in Thailand, namely "Thairath", "Dailynews", and "Khaosod" in terms of their compliance with the WHO’s suicide news reporting guidelines for 2017. Data were analyzed by SPSS using the Chi-square test and Fisher’s exact test. Results: A total of 309 suicide news were reported from Thairath (52.8%), Dailynews (24.9%), and Khaosod (22.3%), with the majority of the population being male, middle adulthood and Thai nationality. The most common methods of suicide were jumping from a height, including jumping into the water (24.6%) and using firearm (23.6%). 89.6% of reports mentioned name of the victim and 57.9% mentioned occupation. 78.0% of them were single suicide and 82.8% were completed suicide. 4.2% of reports provided information about where to seek help, 1.9% educated about suicide and suicide prevention and 1.9% educated about how to cope with life stressors and how to get help. 98.7% of reports presented details of methods and 98.7% mentioned location of suicide. 44% of cases placing reports on the front page, 40.1% using sensational headlines and 28.8% posted images of victims. Conclusion: Overall, newspaper adherence to the WHO media guidelines on reporting suicide in this study were unsatisfactory. Mental health organizations and media bodies are encouraged to work together to improve media reporting of news about suicide in Thailand.